2020
DOI: 10.1186/s12889-020-09502-x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the incidence of diabetes mellitus: results from the Global Burden of Disease Study 2017 and implications for diabetes mellitus prevention

Abstract: Backgroud Diabetes mellitus is a common chronic disease and a severe public health issue. The incidence trends for type 1 diabetes (TIDM) and type 2 diabetes (T2DM) have rarely been studied on a global scale. We aimed to determine the temporal and geographical trends of diabetes globally. Methods Data on diabetes mellitus, including incidence, prevalence from 1990 to 2017 were obtained from the 2017 Global Burden of Disease study. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(123 citation statements)
references
References 40 publications
2
90
1
1
Order By: Relevance
“…Type 2 diabetes (T2D) is a chronic metabolic condition associated with hyperglycemia and insulin resistance, whose incidence is continuously increasing worldwide [ 1 ]. Hyperglycemia is deemed the principal pathogenic factor in T2D since high blood glucose levels are implicated in major health complications including cardiovascular diseases, neuropathy, nephropathy, and retinopathy [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes (T2D) is a chronic metabolic condition associated with hyperglycemia and insulin resistance, whose incidence is continuously increasing worldwide [ 1 ]. Hyperglycemia is deemed the principal pathogenic factor in T2D since high blood glucose levels are implicated in major health complications including cardiovascular diseases, neuropathy, nephropathy, and retinopathy [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the development of this pathology shows high hereditability, T2DM seems to be caused by a combination of lifestyle and genetic factors [ 25 ]. In this sense, T2DM prevalence is increasing in children and younger adults, due to rising levels of obesity, sedentary lifestyle and inappropriate diet [ 26 , 27 ].…”
Section: Prediabetes and Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…On the other hand, db/db mice on IF show a reduction of NFκB activation and decreased LPS levels, associated with a significant improvement of cognitive function, limited neuroinflammatory response, restructured gut microbiota and metabolites [ 27 , 220 ] and reduced insulin resistance [ 207 ]. Other studies in db/db mice on IF regimen for 28 days have reported a reduction of Enterococcus , Streptococcus , Enterococcaceae , Arthromitus , Rummeliibacillus that cause inflammation, while increasing Lactobacillus , accompanied by the attenuation of behavioral alterations [ 207 ].…”
Section: Diet Inflammation and Gut Microbiota In T2dm Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence rates for diabetes mellitus continue to rise across countries and continents ( 1 7 ). This has been exacerbated by over 100% increases in incident cases of diabetes mellitus from 1990, rising to 22.936 million in 2017 ( 8 ), which has resulted in an estimated 463 million people worldwide with diabetes mellitus in 2019 ( 8 , 9 ). These prevalence rates are expected to grow unless addressed.…”
Section: Introductionmentioning
confidence: 99%